Pharmacy Students’ Views on Pilot Interprofessional Learning at a Teaching Hospital in Pahang, Malaysia - Nor Hidayah Mohd Taufek; Norny Syafinaz Ab Rahman; Tengku Karmila Tengku Mohd Kamil; Mohamad Haniki Nik Mohamed; Nur Amni ‘Afifah Mohd Faisal; Christopher John Turner (Journal of Pharmacy)
Introduction: Interprofessional learning (IPL) has been practiced in pharmacy curricula worldwide. The unique approach and design for IPL must be tailored within the context of practice to be effective. This study aimed to explore the reflection of experiences by pharmacy students regarding a pilot interprofessional learning activity at a teaching hospital in Malaysia. Methods: Data were collected from 21 pharmacy students using reflective diaries to explore actual experiences, perceived challenges, and learning. All students completed a four-week pilot IPL activity in a clinical setting at a teaching hospital. Data were extracted, analysed sorted, and coded using Atlas.ti® version 9 and subjected to thematic analysis. Results: Four themes emerged from the data: 1) Professional development and interdisciplinary insight 2) Favourable interprofessional engagement, 3) Valuing the application of IPL, and 4) Operational flaws in IPL implementation. Conclusion: The pilot IPL has become a useful platform for pharmacy students to develop metacognitive skills during interprofessional experiences with students, healthcare professionals, and patients. Improvement in its implementation requires strategies tailored to contextual needs. Future studies are required to ensure continuous assessments of improvised IPL components to prepare competent pharmacists for patient-centred care.